Epidemiology of Nasopharyngeal Carcinoma (NPC) in Pahang, Malaysia - Mohd Yassin, Wardah; Kaderi, Mohd Arifin; A. Rahman, Nor Azlina; Zainuddin, Norafiza; Ahmad, Azmir; Raja Lope Ahmad, Raja Ahmad Al’Konee; Abdullah, Kahairi; Leman, Wan Ishlah; Tolos, Siti Marponga; Rosla, Luqman; Paul, Mark; Yaacob, Nik Soriani; et al. (2016)
Nasopharyngeal carcinoma (NPC) is among the most frequently reported cancer in Malaysia. The most recent National Cancer Registry (NCR), stated that NPC was the fourth most common cancer among Malaysian and third most common cancer among Malaysian men. While there have been several studies on NPC previously carried out in a few states in Malaysia, a comprehensive study in Pahang had never been reported. The current epidemiological study is designed to feature the number of cases and distribution of NPC in Pahang, as well as risk factors of the development of the disease. This study involved two major referral centers in Pahang, namely Hospital Tengku Ampuan Afzan (HTAA) in Kuantan and Hospital Sultan Haji Ahmad Shah (HOSHAS) in Temerloh. A total of 87 confirmed NPC cases were reported from the two hospital between 2012 and 2015. The ages at diagnosis of patients ranged from 14 to 82 years with mean age was 49.4 years (SD ±14.3). Majority of them were male (77%) with ratio male to female was 3.3:1. Regarding ethnicity, Malay predominates with 56%, followed by Chinese 35% and others 9%. The total number of diagnosed cases increased from 2012 to 2014 and declined slightly in 2015. The age-standardised rate (ASR) were calculated every year and showed an increasing trend among male from 1.6 per 100,000 in 2012 to 3.3 per 100,000 in 2015. Generally, the highest age-specific incidence rate was at the 50-54 age groups. Ongoing analysis on available data is currently being carried out to unravel the lifestyle risk factor in this population of NPC patients. This study will hopefully provide the first ever four-year comprehensive data on the epidemiology of NPC in the state of Pahang, Malaysia.